Promoting Local Cuisine on Social Media: A Strategic Communication Approach - Wisnu Widjanarko; Yusida Lusiana; S Bekti Istiyanto; Wiwik Novianti; Lartceva Natalia Evgenievna (Komunikator, 2024)
The rise of food digitization has ushered in a new perspective on the culinary world. Local gastronomic traditions are now showcased globally through social media platforms, presenting opportunities and challenges in terms of cultural representation, authenticity, and global accessibility to diverse cuisines. This research aims to examine the complexities and dynamics involved in digitally promoting local culinary heritage. Its objective is to identify and outline strategies, challenges, and factors essential for navigating the digital culinary landscape. Findings underscore critical subjects including the tension between authenticity and global appeal, the impact of visual aesthetics, ethical dilemmas in representation, and the pivotal role of strategic communication and public engagement in digital promotion. The research underscores the significance of implementing advanced, rational, and strategically conveyed approaches to digitally promote local culinary heritage. In conclusion, this study offers valuable insights with significant implications for chefs, online advertisers, and individuals involved in cultural preservation amid the era of digital globalization.